A curriculum-based virtual and physical mobile learning model for elementary schools in museums. Issue 6 (7th November 2016) - Hsu, Tien-Yu; Kuo, Fan-Ray; Liang, Hsin-Yi; Lee, Min-Feng
Abstract : Purpose: This paper aims to develop a curriculum-based virtual and physical mobile (CVPM) learning model, which integrates related physical and e-learning resources associated with elementary school curricula and supports elementary education. Design/methodology/approach: This model provides a highly participative and well-monitored environment with fruitful interactions among students, teachers and museum staff. A practical system was implemented in the National Museum of Natural Science in Taiwan. Findings: The results show that the proposed model can effectively extend related learning resources to satisfy the requirements of elementary education. In addition, this model can engage students' self-directed explorations through problem-solving learning content during the learning process. Research limitations/implications: This learning model was implemented in a one-day theme-based learning activity. Generic learning outcomes and qualitative analysis were used to examine the students' perceptions and the teachers' feedback of this learning model, respectively. Practical implications: The results show that both students and teachers highly appreciated this learning model. The model not only strengthens the connection between museum and elementary curricula but also enhances students' perceptions and positive attitudes toward natural science courses. Finally, this study offers suggestions for future research. Originality/value: This study develops a CVPM learning model which integrates elementary school courses to satisfy the requirements of elementary education and meet museums' educational strategies for schools. The practical learning system and services have been successfully implemented and are widely available to elementary schools in Taiwan.